Performance Management of Moving Teachers at State Middle School 1 Manado - Tumakaka, Ria Angelia; Katuuk, Deitje A.; Mongdong, Romi J. (Indonesian Journal of Multidisciplinary Science, 2025)
This study aims to analyze the performance management of Leading Teachers at SMP Negeri 1 Manado, focusing on three main aspects: planning, implementation, and evaluation. Leading Teachers is a strategic program of the Ministry of Education, Culture, Research, and Technology that aims to create agents of change in education through instructional leadership, reflection, collaboration, and innovation. In the context of educational management, Leading Teachers are expected to improve teacher professionalism and encourage a transformation in work culture in schools. This study used a qualitative approach with a descriptive design. Data collection techniques included in-depth interviews, observations, and documentation studies with the principal, leading teachers, non-leading teachers, students, and parents. Data analysis was conducted using an interactive model that included data reduction, data presentation, conclusion drawing and verification. The results indicate that Leading Teacher performance planning has been carried out strategically and participatoryly through school work forums and planning documents such as the RKS (Work Plan), RKAS (Work Plan for School Activities), and KOSP (Work Plan for School Activities). Performance implementation reflects the Leading Teacher principles through project-based learning, a differentiated approach, and coaching practices that encourage teacher collaboration and motivation. Performance evaluation is conducted internally through supervision and reflection, and externally through monitoring by the Education Office. This study concludes that the performance management of Leading Teachers positively contributes to improving the quality of education. Structured and collaborative implementation is key to creating a professional, adaptive, and sustainable school ecosystem.